A pilot study of exome sequencing in a diverse New Zealand cohort with undiagnosed disorders and cancer. Issue 4 (2nd October 2018) - McKeown, Colina; Connors, Samantha; Stapleton, Rachel; Morgan, Tim; Hayes, Ian; Neas, Katherine; Dixon, Joanne; Gibson, Kate; Markie, David M.; Tsai, Peter; Blenkiron, Cherie; Fitzgerald, Sandra; et al.
ABSTRACT: We report the results of a pilot project for clinical DNA sequencing in New Zealand. This project aimed to estimate the diagnostic yield of next generation sequencing in the New Zealand clinical environment. Trio whole exome sequencing (WES) was performed on germline DNA of 40 individuals from 12 families with presumptive Mendelian disorders. In addition, both WES and deep targeted sequencing (DTS) was performed on tumours, metastases and corresponding normal blood leukocytes from two cancer patients. For the rare Mendelian disorder cohort, the diagnostic yield was 6/12, including previously recognised pathogenic mutations and novel mutations. In tumour sequence analysis, WES identified somatic single nucleotide mutations and copy number aberrations in both cancer patients; however, DTS was required to obtain clinically informative information. This study showed that diagnostic germline and tumour WES and DTS could be easily undertaken in New Zealand, and identified specific infrastructural challenges that must be solved to facilitate its clinical use.